INTERNAL CONTROL AND THE LEVEL OF EFFECTIVENESS IN THE ORGANIZATIONAL MANAGEMENT OF MSMES - Rios Sanipatin, Emma Lucía; Fonseca Romero, Gabriela Natali; Inca Falconí, Alex Fabián (mktDESCUBRE, 2020)
In Ecuador with the new constitution in force since 2008; the popular and solidarity economy sector with its organizations is part of the country’s economic system. Financial and non-financial organizations have been venturing into the business field and participating in the national and international market; they are subject to the control and supervision of government bodies. The objective of this work is to present the level of effectiveness of the internal control system of Mipymes in the non-financial sector, mountain region, rural area, taking as reference the COSO Model. The object of study was four production organizations. The research carried out was analytical and descriptive; for the collection of the information, the questionnaires were prepared within the conceptual framework of the COSO Model. The results obtained revealed that the internal control system in two organizations reached a non-effective level, an organization reached a partially effective level and the effective level reached an organization. The application of an internal control system that is adaptable to your needs, such as the COSO model, will help to improve the level of effectiveness of internal control together with the periodic evaluation of internal control will allow you to improve organizational management.